INTERCULTURAL COMMUNICATION: MAINTAINING CROSS-CULTURAL HARMONY IN THE WORKPLACE - Diah Ayu Reza Permatasari; Nanang Trenggono, Tina Kartika (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Cultural differences can affect communication in general, making it difficult to reach a solution. Cultural differences can make communication difficult due to misunderstandings between individuals. People who have just moved from their home environment will find it difficult to adapt if they are not used to the changes. Cultural differences in the workplace lead to differences in the way ideas, perceptions and everyday behaviours are communicated. This also means that there are differences in intercultural communication strategies. If the communication strategy used is appropriate, the communication that takes place in the work environment will be more effective. This research uses a descriptive qualitative approach with the object of research being DPW PKB Lampung Province. The research subjects are DPW PKB employees from Lampung, Java, Sunda and Semendo ethnic groups. The data collection techniques used are observation, in-depth interviews, documentation and literature review. Furthermore, the research data analysis used the Miles and Huberman model as a guide for data processing. The results of this study, namely DPW PKB Lampung Province employees, show that students are aware of the importance of effective communication strategies in intercultural interactions. Some informants have implemented some elements of Steve Carteledge's communication strategy in their communication practices with other tribes, such as planning, adaptation, and strategy development. However, some informants still need to increase their awareness or knowledge of best practices in intercultural communication.